Integrating ecosystem services in Swedish environmental assessments: an empirical analysis. Issue 3 (4th May 2018) - Hansen, Karin; Malmaeus, Mikael; Hasselström, Linus; Lindblom, Erik; Norén, Katja; Olshammar, Mikael; Söderqvist, Tore; Soutukorva, Åsa
Abstract: Given the growing number of policies and laws that encourage inclusion of ecosystem services (ES) in processes, we have investigated environmental impact assessments (EIA) and strategic environmental assessments (SEA) conducted in Sweden in order to analyse whether ES may be integrated to enhance and improve environmental assessment of today. Representative Swedish environmental projects were reviewed. Three cases with different geographic and environmental settings were selected to allow us to study consideration of a wide range of different ES. We investigated the processes and discussions taking place using documentation from the cases. We formalized and labelled the expected impacts into an ES framework. Summarizing each case, we described conformities and divergences in explicit and implicit prioritizations between the actors. We discussed the benefits of integrating ES into current practices and possible improvements in the processes and methodologies. When ES could be integrated into EIAs and SEAs more aspects would be visualized and a larger stakeholder engagement stimulated leading to improved support for decision-making.